DIMENSIONS OF WORLD RELIGIONS ACCORDING TO NINIAN SMART: A STUDY IN THE AXIS OF WORK NAMED THE WORLD’S RELIGIONS - Şevket ÖZCAN (Fırat University, 2019)
Ninian Smart is a religious scientist who aims to reach a point where there is value-free judicial value in the sense of religion / religions / religious by making the phenomenological approach dominant in his works. In this contex, the seven-dimensional model of religion that he has used is at the beginning of his methods. This model that he named the “dual model” consists of dimensions practice-ritual, experience-emotional, narrative-mythic, doctrinal-philosophical, ethical-legal, social-institutional and material-artistic. Each dimension in the seven-dimensional model of religion has a large area and is associated with other dimensions. He argues that it is possible to examine all religions through this model and that the presence of these dimensions in all religions can be determined. As all religions, however, have each of these seven dimensions, he draws attention to the fact that more than one dimension is more emphasized. In the sense of this model, the work of The World’s Religions, which features Smart's latest and most comprehensive work comes to the fore. In this work, he seeks to reveal in a holistic, phenomenological manner of the many religious traditions that have manifested themselves in the world in the context of the seven-dimensional religion model. In this direction, he reveals important analyzes of the religions of Hinduism, Buddhism, Judaism and Christianity, which he describes as the great world religions. In this article, Smart's general characteristics of the dimensional analysis of religions in the context of “The World's Religions” are examined. By introducing Smart's seven-dimensional religion model, it is aimed to present a viewpoint to the researchers / readers about the usage of this method.